Tough and hierarchical porous cryogel scaffolds preparation using n-butanol as a non-solvent - Sen, Tugce; Ozcelik, Berkay; Ozmen, Mehmet Murat (TAYLOR & FRANCIS AS, 2019)
Hierarchical porous chitosan cryogels were prepared by combination of cryogelation and phase separation techniques. n-Butanol was included as a non-solvent in the initial polymer solutions to enable phase separation. The internal morphology of the resulting cryogels revealed hierarchical porosity where larger pores of between 25-50 mu m were formed via cryogelation, whereas smaller pores of between 4-10 mu m were produced by phase separation. The control sample prepared without n-butanol exhibited monotype porosity. Any crack development was not observed when samples were compressed up to 80% strain. The results demonstrated hierarchical porous and tough scaffolds with potential use in tissue engineering. [GRAPHICS] .
Keywords: Chitosan; cryogelation; hierarchical; macroporous; phase separation; scaffold; MACROPOROUS POLY(ACRYLAMIDE) HYDROGELS; PHASE-SEPARATION; SILK FIBROIN; DMSO/WATER MIXTURE; TISSUE; FABRICATION; Materials Science; Polymer Science